German Jews : a dual identity - Mendes-Flohr, Paul R. (Yale University Press, 1999)
In this book the author explores through the prism of Rosenweig's image of how German Jews have understood and contended with their two-fold spiritual patrimony. He deepens the discussion to consider also how the German-Jewish experience bears upon the general random experience of living with multiple cultural identities.
Keywords: Rosenzweig, Franz, -- 1886-1929.; Rosenzweig, Franz, -- 1886-1929; Jews -- Germany -- Identity.; Jews -- Cultural assimilation -- Germany.; Germany -- Ethnic relations.; Juifs -- Allemagne -- Identité.; Juifs -- Acculturation -- Allemagne.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; HISTORY -- Jewish.; Ethnic relations; Jews -- Cultural assimilation; Jews -- Identity; Germany; Joden.; Identiteit.; Duitsland.